2015
DOI: 10.1103/physreva.91.043612
|View full text |Cite
|
Sign up to set email alerts
|

Pairing correlations in a trapped one-dimensional Fermi gas

Abstract: We use a BCS-type variational wavefunction to study attractively-interacting quasi onedimensional (1D) fermionic atomic gases, motivated by cold-atom experiments that access the 1D regime using an anisotropic harmonic trapping potential (with trapping frequencies ωx = ωy ωz) that confines the gas to a cigar-shaped geometry. To handle the presence of the trap along the zdirection, we construct our variational wavefunction from the harmonic oscillator Hermite functions that are the eigenstates of the single-part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…2a. We find a local density and pairing amplitude that are spatially inhomogeneous due to the imposed trapping potential, with shapes that are consistent with earlier work based on mean-field theory and Bethe ansatz [59]. Furthermore, the one-body density and pairing matrices are mostly diagonal in index space.…”
Section: A Harmonic Trapsupporting
confidence: 88%
“…2a. We find a local density and pairing amplitude that are spatially inhomogeneous due to the imposed trapping potential, with shapes that are consistent with earlier work based on mean-field theory and Bethe ansatz [59]. Furthermore, the one-body density and pairing matrices are mostly diagonal in index space.…”
Section: A Harmonic Trapsupporting
confidence: 88%
“…In Ref. [51] the balanced case was studied using a similar variational wave function. It was found that including this additional variational parameter was necessary to allow the cloud size to decrease with increasing strength of attraction (which is what is expected on physical grounds and is observed experimentally).…”
Section: Variational Energymentioning
confidence: 99%
“…[51] it was shown that a simple variational BCStype wave function that involved pairing of harmonicoscillator states could account for pairing correlations in a balanced trapped 1D gas without the necessity of invoking the LDA. Here, we propose a similar wave function for the imbalanced case that incorporates FFLO pairing correlations in a natural way.…”
Section: Introductionmentioning
confidence: 99%
“…have been of much interest as they can be measured in experiment and are, within mean-field theory, directly proportional to the gap C kγ,pσ = δ k,−p δ γ,σ |∆| 2 /(4E 2 k,γ ) [12][13][14][15][16][17][18]. We compute the time-evolved density-density correlations C kγ,pσ (t) by inserting the exponentials e itH(J f ,J f ,U f ) inside all expectation values in Eq.…”
Section: Time Evolution Of the Density-density Correlation Functionmentioning
confidence: 99%
“…Greiner et al have demonstrated that measuring the shot noise in absorption images makes the densitydensity correlations experimentally accessible [13]. This has motivated several further studies of the density-density correlations [14][15][16] as well as proposals to use them in order to distinguish different phases of ultracold fermions [17][18][19][20]. An alternative approach to measuring the correlations in a Fermionic gas is to observe the time-evoulution after a quench of either the lattice depth or the interactions between atoms.…”
Section: Introductionmentioning
confidence: 99%